International Law Standards for Obtaining of Electronic Evidence from Foreign Jurisdictions (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the features of the interaction of the competent criminal prosecution authorities with foreign jurisdictions and international legal standards for the execution of letter of request in order to obtain electronic evidence, as well as international initiatives and agreements aimed at combating crimes using computer networks.